SISTEM CASE BASED REASONING UNTUK MENDIAGNOSIS PENYAKIT ANJING BERBASIS WEB - Dwi C Djahilape; Derwin R Sina; Tiwuk Widiastuti (J-ICON : Jurnal Komputer dan Informatika, 2016)
The design of medium for consultation purpose is firstly caused by the lack of society awareness of dogs’ disease, their responsibility to regularly take care of the pet when it sufferred a disease and the cost of care. This medium care is the application of Case Based Reasoning (CBR). CBR is kind of reasoning used to solve a new problem by adapting the solutions found in the previous cases through summing the similarities. In this research the Simple Matching Coefficient (SMC) method is employed to count the similarities. This Case Based Reasoning application will produce the output like kind of disease sufferered by dogs based on symptoms reported by the proprietor. Furthermore, the application serve you with the solution of medical care. This application is a web based with aims to facilitate the user to access the information needed easily. The system trial showing that the program can do the diagnose well according to symptoms reported. The result of the diagnose is also provided with the similarities percentage with the previous case. This aims to improve the level of validity and the accurateness of disease found in dogs.